rozwiąż równanie i sprawdź otrzymane rozwiązanie
a) 3 - ( x - 3) = x - 3
b) (x+3) - (3-x) = x
c) (2x - 1) + (1-2) = x
proszę o pomoc w tych 3 przykładach daje naj ​


Odpowiedź :

Odpowiedź:

a)

3 - ( x - 3) = x - 3

3 - x + 3 = x - 3

-x - x = -3 - 6

-2x = -9     /:(-2)

x = 9/2 = 4 1/2

spr.

L = 3 - (4 1/2 - 3) = 3 - 1 1/2 = 1 1/2

P = 4 1/2 - 3 = 1 1/2

L = P

b)

(x+3) - (3-x) = x

x + 3 - 3 + x = x

2x - x = 0

x = 0

spr.

L = (0 + 3) - (3 - 0) = 3 - 3 = 0

P = 0

L = P

c)

(2x - 1) + (1-2) = x

2x - 1 - 1 = x

2x - x = 2

x = 2

spr.

L = (2 * 2 - 1) - 1 = 4 - 1 - 1 = 2

P = 2

L = P

Szczegolowe wyjaśnienie: